1980
DOI: 10.5636/jgg.32.217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the relations between the changes of the geomagnetic field, solar corpuscular radiation, atmospheric circulation, and climate.

Abstract: The correlations between geomagnetic, climatic, and meteorological phenomena were investigated with the object of demonstrating the function of the geomagnetic pole and changes of its position in controlling the climate and weather. A tentative model has been proposed to enable one to understand the causes of the generation of glacial and interglacial periods, as well as the causes which effect changes of climate (BUCHA, 1976a).The analyses of various types of geomagnetic and atmospheric manifestations have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Published virtual pole position paths over archeological time scales such as by KAWAI et al (1965), NODIA and CHELIDLE (1972) or, more recently, by KOVACHEVA (1980) and BUCHA (1980) are quite complex. The path complexity, reflecting clockwise and counterclockwise motions, has been attributed to nondipole field contributions, a wobbling dipole field and sporadic coverage of archeological sites.…”
Section: Migration Of Virtual Geomagnetic Poles During Historic and Pmentioning
confidence: 99%
“…Published virtual pole position paths over archeological time scales such as by KAWAI et al (1965), NODIA and CHELIDLE (1972) or, more recently, by KOVACHEVA (1980) and BUCHA (1980) are quite complex. The path complexity, reflecting clockwise and counterclockwise motions, has been attributed to nondipole field contributions, a wobbling dipole field and sporadic coverage of archeological sites.…”
Section: Migration Of Virtual Geomagnetic Poles During Historic and Pmentioning
confidence: 99%
“…Hunter [89] has suggested that weather and climate on Earth were influenced by geomagnetic-solar activity and later particularly in the troposphere [90,91] and perhaps more specifically Labitze & van Loon [92,93] made the possible connection with the 11-year solar cycle as did FriisChristensen & Lassen [94]. The work by Grafe & Heider [95] has suggested a 6-y delay in global temperature compared with geomagnetic activity which may, along with local geographic factors, allow some planning in agriculture production strategy that will be needed especially if the projected estimates of the FAO of 9 billion people requiring nutrition is correct.…”
Section: Chronobiology and Chronomicsmentioning
confidence: 99%